Investigating ice formation pathways using a novel two-moment multi-class cloud microphysics scheme - T. Lüttmer; P. Spichtinger; A. Seifert (Atmospheric Chemistry and Physics)
For pure ice clouds in the cold-temperature regime (T<235 K), two major formation pathways are possible. Liquid origin ice clouds stem from droplets that freeze close to water saturation. In-situ-formed ice clouds form directly from the vapor phase below water saturation. For a better investigation of these pathways, we developed a novel microphysics scheme. The new two-moment scheme distinguishes between five ice classes (“ice modes”) each with their own unique formation mechanism: homogeneous freezing of solution droplets, deposition nucleation, homogeneous freezing of cloud droplets and raindrops, immersion freezing, and secondary ice from rime splintering. The ice modes interact with each other, e.g., in competition for growth by deposition of water vapor and aggregation, but also with the other cloud particle classes, i.e., cloud droplets, rain, snow, graupel, and hail.